Comparative Efficacy of Dexmedetomidine and Fentanyl for Extubation in Post-Neurosurgical Intensive Care Unit (Community Based Medical Journal, 2025)
The process of extubation in post-neurosurgical patients in the intensive care unit (ICU) requires careful management to ensure patient safety and comfort. Dexmedetomidine and fentanyl are two commonly used medications for sedation and analgesia during extubation. This prospective, randomized, single blind trial was conducted in the Department of Anaesthesiology, Community Based Medical College, Mymensingh, Bangladesh, between January and December of 2023, to compare the efficacy and safety of dexmedetomidine and fentanyl in post-neurosurgical ICU. The study was carried out among 50 post-neurosurgical patients requiring extubation after elective ventilation in neurosurgical ICU in a tertiary care hospital in Bangladesh. A total of 50 patients were included in this study. Inclusion criteria involved patients aged between 18 and 40 years, fairly classified as ASA (American Society of Anesthesiologists) physical status I or II, and undergone elective mechanical ventilation for less than 24 hours following any neurosurgical procedure. However, we excluded patients if they had unstable hemodynamic conditions, a Glasgow Coma Score (GCS) of